Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Minat Beli Ulang Konsumen dengan Kepuasan Pelanggan sebagai Variabel Intervening pada GFC Kabupaten Sidenreng Rappang - Aisyah Abidin; Anwar Anwar; Ilma Wulansari Hasdiansa; Chalid Imran Musa; Rahmat Riwayat Abadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of product quality and service quality on consumer repurchase intention, both directly and through customer satisfaction as an intervening variable at GFC in Sidenreng Rappang Regency. The research method used a quantitative approach with an explanatory design and cross-sectional survey study type. The sampling technique was purposive sampling with a total sample of 270 respondents. Data were collected through questionnaire distribution using a 1-5 Likert scale and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed that: (1) product quality has a positive and significant effect on repurchase intention (β=0.274; t=3.910; p=0.000); (2) service quality has a positive and significant effect on repurchase intention (β=0.279; t=4.416; p=0.000); (3) customer satisfaction has a positive and significant effect on repurchase intention (β=0.387; t=5.457; p=0.000); (4) product quality has a positive and significant effect on customer satisfaction (β=0.246; t=3.129; p=0.002); (5) service quality has a positive and significant effect on customer satisfaction (β=0.409; t=5.546; p=0.000); (6) customer satisfaction mediates the effect of product quality on repurchase intention (β=0.095; t=2.633; p=0.008); and (7) customer satisfaction mediates the effect of service quality on repurchase intention (β=0.158; t=3.671; p=0.000). The R² value of repurchase intention (0.588) and customer satisfaction (0.328) indicates adequate predictive capability.